Організаційно-технологічні основи вдосконалення планування реалізації об`єктів будівництва - Тугай, О. А.; Чуприна, Ю. А.; Горбач, М. В. (Ways to Improve Construction Efficiency, 2014)
Grounded methodology of concept and controlling, allowing relying on them to improve the management system construction projects, particularly in organizational and technological training.